(untitled) (Applied Biological Research, 2023)
An experiment was conducted to study the impact of gamma (γ) rays on some quantitative traits such as germination and survival of seeds; morpho physiological and yield attributes of Indian mustard (Brassica juncea L.). Two varieties of B.juncea viz., ‘Pusa Bold’ and ‘Kranti’, were used in the present study. The seeds of Brassica were irradiated witvarious doses of γ ray (900, 1000, 1100 and 1200 Gy) and a combination treatment with ethyl methane sulfonate (1000 Gy + 2% EMS). The control seeds were not exposed to either radiation or EMS. The results revealed that dosesof γ radiation altered all the studied traits for both the tested varieties. Increasing doses of γ-radiation were responsible for decreasing the seed germination, plant survival, plant height, number of siliqua plant-1, seed siliqua-1dry weight of whole plant, SPAD value, weight of dry husk plant-1, leaf area and photosynthetic rate. Plants in M1 generation indicated dose dependent physiological changes of genotype as compared to the control. Thisalternation of each traits indicated that γ-radiation has some effect on Brassica seeds which might be utilized asmutant for future variety development programme.